A unique case of splenic tumor exhibiting a serous carcinoma phenotype. (May 2021) - Kawashima, Keisuke; Kito, Yusuke; Tochii, Koya; Kimura, Masaki; Takeda, Taro; Sekino, Takafumi; Ikeda, Tsuneko; Takeuchi, Tamotsu
The spleen has no epithelial element; thus, primary carcinoma of the spleen is quite rare. We present the case of a patient with serous carcinoma of the spleen. A 76-year-old woman with no significant medical history presented with a huge lesion in the spleen. Except this lesion, clinical examination, including imaging examination, revealed no remarkable findings. She underwent excision of the spleen for treatment and diagnosis. Postoperative pathological examination revealed neoplastic cells with pleomorphic and hyperchromatic nuclei, prominent nucleoli, and frequent mitotic activity. The neoplastic cells exhibited a papillary pattern with psammoma bodies. Immunohistochemistry showed positivity for cytokeratin 7, PAX-8, WT-1, p16, p53, and Ber-EP4 and negativity for cytokeratin 20, thyroid transcription factor-1, carcinoembryonic antigen, CD10, estrogen receptor, calretinin, D2-40, intelectin-1, and sialylated HEG1. We inferred that this tumor was a primary splenic serous carcinoma. Serous tubal intraepithelial carcinoma is the plausible origin of most pelvic serous carcinomas. However, the origin of serous carcinoma of the spleen remains unknown. We speculated that endosalpingiosis might be the origin of the tumor.